the Faktor-Faktor yang Berpengaruh terhadap Adverse Drug Reaction pada penggunaan Obat Anti Tuberkulosis - Lucia Vita Inandha Dewi (Fakultas Farmasi Universitas Setia Budi, 2020)
Adverse Drug Reaction (ADR) in the treatment of tuberculosis can reduce the quality of life and compliance of patients, long-term treatment has a risk of ADR, to prevent dangerous ADRs need to be monitored properly, the predictors that affect ADR are very important to be sought as an effort to prevent the incidence ADR. This study was a cross-sectional study conducted on pulmonary tuberculosis patients at the Public Health Center (PKM) of Bantul Regency Yogyakarta, inclusion criteria were patients who received fixed-dose combination tuberculosis (KDT), age> 17 years old, ADR monitoring was carried out since the month of two treatments up to the 6th month by interview method for each control patient to the PKM. Data processing was performed by multinomial regression multivariate tests. The results showed that ADR occurred in 58% of the old age group; 51.8% of the middle age group and 50% of the young age group, there was no significant effect of age on ADR in this study. Based on sex, ADR occurred in 58.5% of men, and 47.3% of women, with no significant effect of gender on ADR. Based on BMI, ADR occurred in the underweight, normal, and overweight groups with a percentage of 78%, 26%, and 40% there was a significant influence between BMI and the incidence of ADR, p-value 0.01 OR = 7,650 (2,350-24,898) CI = 95 %. Based on the BTA ADR group occurred in the positive and negative BTA groups with a percentage of 52% and 62%, there was no significant effect between the BTA and the ADR incidence Key words : Adverse Drug Reaction, Tuberculosis, Fixed-dosed combination-Antituberculosis Drug (FDC)